Nintedanib reduces radiation-induced microscopic lung fibrosis but this cannot be monitored by CT imaging: A preclinical study with a high precision image-guided irradiator. Issue 3 (September 2017) - De Ruysscher, Dirk; Granton, Patrick Vincent; Lieuwes, Natasja Gaby; van Hoof, Stefan; Wollin, Lutz; Weynand, Birgit; Dingemans, Anne-Marie; Verhaegen, Frank; Dubois, Ludwig
Abstract: Background: Nintedanib has anti-fibrotic and anti-inflammatory activity and is approved for the treatment of idiopathic pulmonary fibrosis. The aim of this study was to noninvasively assess the efficacy of nintedanib in a mouse model of partial lung irradiation to prevent radiation-induced lung damage (RILD). Methods: 266 C57BL/6 adult male mice were irradiated with a single radiation dose (0, 4, 8, 12, 16 or 20 Gy) using parallel-opposed fields targeting the upper right lung using a precision image-guided small animal irradiator sparing heart and spine based on micro-CT images. One week post irradiation, mice were randomized across nintedanib daily oral gavage treatment (0, 30 or 60 mg/kg). CT density analysis of the lungs was performed on monthly acquired micro-CT images. After 39 weeks, lungs were processed to evaluate the fibrotic phenotype. Results: Although the CT density increase correlated with the radiation dose, nintedanib did not influence this relationship. Immunohistochemical analysis confirmed the ability of nintedanib to reduce the microscopic fibrotic phenotype, in particular interstitial edema, interstitial and perivascular fibrosis and inflammation, and vasculitis. Conclusions: Nintedanib reduces radiation-induced lung fibrosis after partial lung irradiation without adverse effects, however, noninvasive CT imaging measuring electron density cannot be applied for monitoring its effects.